PEMBELAJARAN KOSAKATA BAHASA PRANCIS DENGAN MEDIA FLASHCARD (STUDI KASUS PADA MAHASISWA SASTRA PRANCIS) - Ardiyanti, Azisah; Bandu, Irianti; Usman, Moses (Universitas Hasanuddin, 2018)
This study aims to determine the effect of using flashcard as a medium of learning French vocabulary by comparing test results before and after using flashcard. The subject of this research is the second semester French students. There are 4 materials test: body parts, animals, daily activities, and clothing. The results of the test were compared with test results before using a flashcard and analyzed using quantitative descriptive methods. The results of this study indicate that the average value of respondents after using flashcard has increased. With the increase, it can be said that flashcard is one interesting alternative to enable students to remember and understand French vocabulary.